SENI TEREBANG GEBES GRUP CANDRALIJAYA DI KAMPUNG CIRANGKONG DESA CIKEUSAL KECAMATAN TANJUNGJAYA KABUPATEN TASIKMALAYA - Asti Tri Lestari (Magelaran: Jurnal Pendidikan Seni, 2019)
This research is intended to find out the development of art in the gebes in Cirangkong Village, Cikeusal Village, Tanjung Jaya District, Tasikmalaya Regency. This has become important regarding the art of gebes which is a product of local communities whose existence is now increasingly marginalized by the invasion of foreign cultures as a result of globalization. The research method used is descriptive method with a qualitative approach. Based on the data collected successfully, it is illustrated that the art of gebes felling has a function as a ritual in the celebration of harvest for the supporting community. A new phenomenon that is as entertainment in enlivening various national events. Another symptom of the emergence of art groups was broken down in schools played by school students. The structure of the performance of the art is broken down in the event of the purpose of overtime, which starts from the preparation, implementation, and closing.